The Lasting Calculation Optimization for Wood Poles in Power Lines Designing (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Power lines in company „Latvenergo” are designed by program STAAD-111. Information involved in program contains data about the length of wood poles, wood poles strength rate, space between wood poles, the region of wind where the designed power line is intended to be exploited, the division of wood poles in the investigation stages where the data about strength parametrs are needed, the type of wires, the wood pole density, the wood pole module of flexibility . Following parameters are calculated: the support connection reactions, shear resistance, twist moment, bending tension and combined tension. After the analyses of results the assumptive load is applied on wood poles in three- dimension plane is determined. For power lines design optimization there are offered: ? the calculation data based on experimentally obtained wood strength parametrs; ? the statistical appreciation and strength parameters estimation model which is based on technological process distribution into control points; ? the calculation algorithm for the project programm STAAD-111 based on experimentally obtained wood strength parametrs.